Gynaecological cancer and night shift work: A systematic review. (April 2018) - Schwarz, Christine; Pedraza-Flechas, Ana María; Lope, Virginia; Pastor-Barriuso, Roberto; Pollan, Marina; Perez-Gomez, Beatriz
Highlights: We explored the possible link between night shift work and gynaecological cancer. Our systematic review retrieved only relevant seven articles, which provided data from just six studies. The relationship between night shift work and ovarian, endometrial or cervical cancer remains unclear. Abstract: Night shift work can affect hormonal balance, and so might be a risk factor for gynaecological malignancies. This report presents a systematic review on the association between this occupational exposure and the incidence of gynaecological cancers other than breast cancer. We searched for original articles addressing this issue in PubMed/MEDLINE, EMBASE and Web of Science, and used the Newcastle–Ottawa Quality Index to evaluate the methodological quality of those reports selected for review. Globally, we found only six articles, which provided the results of just six research studies: four examined ovarian cancer, two endometrial tumours and two cervical cancer. Our results show that this matter has received scant attention from the research community, and that the little evidence available does not show any clear relationship between night shift work and ovarian, endometrial or cervical cancer. More prospective rigorous studies are needed to evaluate these associations.